(untitled) (KONFERENSIYA, 2025)
This article explores William Shakespeare’s works and their key themes, which have inspired writers and left a lasting impression on readers. Additionally, it discusses the reinterpretation of Shakespeare’s works in theatre and cinema, highlighting innovative staging’s and cinematic retellings. The article also examines critical perspectives, including Harold Bloom’s skepticism toward modern adaptations and Kiernan Ryan’s analysis of Shakespeare’s evolving cultural relevance. By addressing these aspects, it underscores why Shakespeare remains a central figure in literary studies and popular culture today